Research progress on fertilizer carbon emissions: a bibliometric analysis (2008–2024) - Yang, Lin; Wang, Zhanbo; Cui, Yuhu; Song, Yan; Zhou, Li; Wu, Wentao; Zeng, Xibai; Liu, Zhaohui; Wan, Guangxue (Frontiers in Environmental Science, 2025)
Fertilizers are a major source of agricultural carbon emissions, yet fertilizer carbon emissions (FCE) research remains fragmented and lacks systematic overview, despite its importance for climate mitigation. This paper selects 2,494 related literature in the Web of Science from 2008 to 2024. It reveals the research hotspots and development trends in the field of FCE based on CiteSpace. The results show that: (1) The number of published papers in this field has shown an exponential upward trend, which can be divided into three stages: the infancy stage, the steady development stage, and the rapid growth stage of research. (2) China and the United States emerge as dominant contributors, reflecting their dual roles as major emitters and key drivers of scientific innovation. While high-yield authors form tight collaboration clusters, overall author cooperation remains limited, suggesting the need for greater cross-institutional and interdisciplinary synergy. (3) Co-citation and keyword analyses indicate that the dominant research hotspots include nitrous oxide emissions, fertilizer types, soil carbon cycles, and life-cycle carbon footprint assessment. Cluster and burst analyses reveal a growing emphasis on precision agriculture, emission reduction strategies, and sustainable soil management. This study outlines the trajectory and key areas of focus in FCE research, providing theoretical and methodological support for advancing regenerative agriculture and achieving a low-carbon agricultural transformation. The findings provide a valuable reference for scholars, policymakers, and practitioners seeking to enhance emission reduction strategies and promote sustainable land use globally.